Redesign Interior Asian Spa Center di Bali - Poppy F.Nilasari, Elita Catharina Martino Dwi Nugroho (Intra, 2014)
Busyness and metropolitan lifestyle society today command critical thinking and active motion are often the cause of physical fatigue and pressure so that cause stress and depression. For it is necessary needs a tool that can provide the facilities of revitalization which provide comfort, tranquility and peace physical and psychological. Taking the concept of each country who is the pionerr of rejuvenating techniques like Japan, China, Thailand and Indonesia. Starting from the creating atmosphere that support the revitalization of the Rejuvenating of every client who comes, to optimize the natural modern design that gives the impression of relaxed , calm and hommy. Asian Spa Center is expected to be the only place that offers Rejuvenating spa themselves through a culture, and a country which is traditional and typical and also can satisfy the current needs of the Surabaya societyÂ in terms of relaxation and recreation because of tired and stress.Â